INTERVIEW: MIHAI IOVĂNEL - Mihai, IOVĂNEL (Studia Universitatis Babeș-Bolyai Philologia, 2022)
Q: Literary history, be it national, local, or regional, is perhaps the most conservative form of literary study, with many claiming that the method is outmoded. What can literary histories do to overcome both the risk of obsolescence and their inherent conservatism? A: I do not believe conservatism is intrinsic to literary historiography. Eugen Lovinescu’s literary histories (1926-1929)—to invoke the most important Romanian contributions—are far from conservative. Directed against the fetishization of tradition, their theoretical starting points are still hard to assimilate by some Romanian cultural institutions to this day. The Romanian Academy is one such institution despite its eagerness to appoint Lovinescu as Member of Honor within its ranks after the 1989 regime change. Nonetheless, it is true that literary history oftentimes ends up playing a conservative role on account of its own history, which is longer and more indebted to the past than that of other forms of literary research. After all, as is well known, what is initially fresh and innovative becomes the object of consecration once it has been ratified and canonized by cultural structures and institutions.